Kelvin Probe Force Microscopy Measuring and Compensating Electrostatic Forces - Sadewasser, Sascha; Glatzel, Thilo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
In the nearly 20 years of Kelvin probe force microscopy an increasing interest in the technique and its applications has developed. This book gives a concise introduction into the method and describes various experimental techniques. Surface potential studies on semiconductor materials, nanostructures and devices are described, as well as application to molecular and organic materials. The current state of surface potential at the atomic scale is also considered. This book presents an excellent introduction for the newcomer to this field, as much as a valuable resource for the expert.
Introduction -- I. Technical Aspects -- Experimental technique and working modes -- Phase Modulation Kelvin Probe Microscopy -- Data interpretation, spatial resolution and deconvolution -- Contribution of the numerical approach to Kelvin probe force microscopies -- Quantum mechanical simulations of electrostatic tip-sample interactions -- II. Selected Applications -- Surface properties of III-V semiconductors -- Electronic surface properties of semiconductors devices -- Optoelectronic studies of solar cells -- Electrical characterization of low dimensional systems (quantum/nano-structures) -- Electronic structure of molecular assemblies -- KPFM for biochemical analysis -- Local work function analysis of photo catalysts -- Kelvin probe force microscopy with atomic resolution -- Summary.
Keywords: Thermodynamics; Engineering; Surfaces (Physics).; Materials Science; Surfaces and Interfaces, Thin Films; Thermodynamics; Engineering Thermodynamics, Heat and Mass Transfer